Prosedur Pemberian Pembiayaan Tanpa Agunan di BTPN Syariah Surabaya - Ningrum, Yunita Kusman; Wahyuni, Rinda Tri; Salasiah, Salasiah (Jurnal Keuangan dan Perbankan Syariah, 2023)
In the last five years BTPN Syariah has continuded to show progress, from year to year the assets of BTPN Syariah have continued to grow accompanied by in increase in distribused financing. Nevertheless, the existing NPF indicates that the soundness level of BTPN Syariah is Collateral-free financing. Therefore, the purpose of this study is to know and understand what kind of procedures are carrier out for collateral-free financing and the financing system. The method used in this research is descriptive qualitative method wiht type of field research (field research), the research technique used is observation and in-depth interviews. The results of the study show that some of the provisions imposed by btpn Syariah can minimizw problematic financing, such as mandatory central meetings, group member selection, and also a group financing system.